The Study on Exception Clauses of Cross-Border Data Flows in International Trade Agreements - Sun, Qi (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This article mainly tells about the definition and characteristics of cross-border data flows, and analyzes different governance models by using comparative methods, for example, it lists America, EU and China’s governance models, because each economy entity represents the different model. The international agreement was signed by many countries, and different countries have their own governance models due to different considerations. So in the international agreement, it has different exception clauses lies in various international trade agreements. And these agreements can be divided into the WTO Agreements and other regional agreements. According to the comparison methodology, this article analyzes the common application dilemmas and thus promotes the construction of an international order for cross-border data flow.